2011
DOI: 10.4269/ajtmh.2011.10-0519
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Human Immunodeficiency Virus–Infected and Uninfected Women in Rwanda

Abstract: Abstract. To determine the prevalence and risk factors of anemia among human immunodeficiency virus (HIV)-infected women in Rwanda and the influence of highly active antiretroviral therapy (HAART) on anemia, we analyzed 200 HIV-positive women and 50 HIV-negative women in a cross-sectional study. Clinical examinations and iron and vitamin B 12 assays were performed, and complete blood counts, serum folic acid levels, and CD4 cell count determined. The prevalence of anemia was significantly higher among HIV-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
42
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 28 publications
17
42
0
2
Order By: Relevance
“…Recepients of zidovudine are more likely to experience anemia and neutropenia than stavudine. [2] The severity of anemia in HIV patients depends on the clinical and immunologic stage of the disease, worsening in the presence of most opportunistic infection or low CD4 cell count and is highly prevalent in patients with low BMI. [2] The studies have found that HAART was an effective treatment for anemia of HIV infection except for the well-known suppressive potential in a few cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recepients of zidovudine are more likely to experience anemia and neutropenia than stavudine. [2] The severity of anemia in HIV patients depends on the clinical and immunologic stage of the disease, worsening in the presence of most opportunistic infection or low CD4 cell count and is highly prevalent in patients with low BMI. [2] The studies have found that HAART was an effective treatment for anemia of HIV infection except for the well-known suppressive potential in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The severity of anemia in HIV patients depends on the clinical and immunologic stage of the disease, worsening in the presence of most opportunistic infection or low CD4 cell count and is highly prevalent in patients with low BMI. [2] The studies have found that HAART was an effective treatment for anemia of HIV infection except for the well-known suppressive potential in a few cases. [2] Increased incidence of anemia, thrombocytopenia and pancytopenia was noted in ART cases as compared to non-art cases.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia was observed in 91.4% of HIVseropositive patients with CD4 cell counts less than 200 cells/mm 3 . 8,10 This study was conducted to evaluate therisk of anemia in human immunodeficiency virus (HIV) infection patients with different CD 4 cell counts after AZT therapy.…”
Section: Wedayani Et Al Risk Of Zidovudine-induced Anemia On Human mentioning
confidence: 99%
“…Female patient has been found to be a risk factor for anemia in some studies. [6][7][8] Another factor currently associated with anemia in HIV patients is CD 4 cell counts. It was reported that 3.2% of asymptomatic HIVseropositive patients with CD 4 cell counts greater than 700 cells/mm 3 were anemic, where as anemia was observed in 20.9% of those with CD 4 cell counts less than 249 cells/ mm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…У большинства больных гепатитом С, включая ВИЧ-инфицированных, развивается стойкая анемия [12,25,26,32,34], усугубляющаяся приёмом токсических препаратов.…”
unclassified